Medication Reconciliation Process Development of the Outpatient Cases with Hypertension in Community Hospitals - Singhirunnusorn, Chaiwat; Arunmuang, Arunrut (Journal of Health Science of Thailand, 2017)
Hypertension is a crucial chronic disease, and is common in elderly patients aged over 60 years. Most hypertensive patients need to take many medicines continuously as a life long treatment. Medication errors occur frequently among the patients and worsen their disease condition. Medication reconciliation process helps the hypertensive patients take their medicine correctly, continuously and regularly as prescribed. The target blood pressure level of the patients as set by the Thai hypertension society can be achieved as a desirable result of the process. In addition medication reconciliation process can save cost of medicine from unnecessary and erroneously use of medicines. Medication reconciliation has been in use for in-patients in community hospitals in Chainat province. With continuous increase in hypertensive patients receiving out-patients (OPD) services and frequent observations of incorrect medicine consumption among the patients, the authored had conducted this study with an objective to apply medication reconciliation process for OPD cases. All 5 community hospitals in the province participated the study. In the process, common pharmacy service standard procedure set under preliminary project named, “the brown bag project” was incorporated in the medication reconciliation process of the hospitals. Effectiveness of the process was measured by the outcomes of patients achieving target blood pressure level, and the saving of medicine cost. The process began by providing medication record book, brown bag and drug counseling to each patient at first visit; followed by the assessments of blood pressure and compliance in 3 consecutive appointments. It was found that by the end of the study most patients were able to control their blood pressure to the desired level. The amount of left over medicines was decreased leading to 86.07% saving of the drug cost; and 86.80% of the patients brought their medication record book and brown bag with them on subsequent appointment visits. The patients had gain better knowledge regarding their illness and the use of medicines, as well as higher satisfaction on the medication reconciliation process. In conclusion, medication reconciliation for out-patient services could be a beneficial process to improve the quality of pharmaceutical services and standardize service practice.